Artificial Skin: Ionic Skin with Biomimetic Dielectric Layer Templated from Calathea Zebrine Leaf (Adv. Funct. Mater. 37/2018). (10th September 2018) - Qiu, Zhiguang; Wan, Yongbiao; Zhou, Wohua; Yang, Jingyi; Yang, Junlong; Huang, Jun; Zhang, Jianming; Liu, Qingxian; Huang, Siya; Bai, Ningning; Wu, Zhigang; Hong, Wei; et al.
Abstract : In article number1802343, Chuan Fei Guo and co‐workers report a new approach to artificial skin based on the unique leaf structure of Calathea zebrine . Fast response time, a very low limit of detection and good sensitivity promise application of the artificial skin in human–machine interaction, motion detection, and artificial intelligence.